POSTOPERATIVE SEPTIC COMPLICATIONS DURING CATARACT TREATMENT - Кирилл Сергеевич Шахматов; Наталья Владимировна Тюнина; Елена Владимировна Громакина; Яна Викторовна Насибян; Надежда Геннадьевна Налимова; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес; Алеся Анатольевна Николаева (Медицина в Кузбассе)
A retrospective analysis of the data of 84859 cases histories of adult patients operated on for cataracts in the ophthalmological departments of the Kuzbass Clinical Hospital named after S.V. Belyaev for the 10-year period (2012-2021). The frequency of postoperative purulent-septic complications in the early postoperative period after cataract extraction was 0.015 % over a 10-year period. Among persons with purulent-septic complications, a high frequency of comorbid pathology was noted: type 2 diabetes mellitus in 40 %, hypertension in 66.6 %, psoriatic arthritis in 13.3 %, and chronic maxillary etmoiditis in 26.6 %.